Peran Kearifan Lokal Masyarakat Suku Mentawai dalam Upaya Mitigasi Bencana: Sistematik Review - Surya Eka Putra; Indang Dewata; Eri Barlian; Nurhasan Syah; Siti Fatimah; Erianjoni Erianjoni; Iswandi U; Muhamad Sholichin (Universitas Riau, 2023)
The disaster that occurred in the Mentawai Islands district has become a cultural shaping factor. Thus, this forms local wisdom to survive and adapt to natural disasters that often occur. This study aims to determine the role of local wisdom in the Mentawai people in disaster mitigation efforts. This type of research is research that uses a systematic review method (Systematic Review). The stages of literature collection refer to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. This study shows that there are several local pearls of wisdom in the form of disaster mitigation that are owned by the Mentawai people, including the arat sabulungan belief that teaches humans to treat nature, plants, water, and animals like him. In addition, there is an Umma (Mentawai Tribe Community House) which was built in a collaborative manner made from natural materials obtained from the forest with the building construction being strong and flexible enough so that it can withstand earthquake shocks. Apart from that, there is the Mentawai Folklore (Sitakkigagailau and Pagetasabbau) which is a picture of their cosmology towards the harmony of life with the natural, social and cultural environment. Based on the results of the study found, it can be concluded that the local wisdom of the Mentawai people plays an important role in mitigating disasters that occur in the Mentawai archipelago district.